AIB1/SRC-3/NCOA3 function in estrogen receptor alpha positive breast cancer - Kiliti, Amber J.; Sharif, Ghada M.; Martin, Mary Beth; Wellstein, Anton; Riegel, Anna T. (Frontiers in Endocrinology, 2023)
The estrogen receptor alpha (ERα) is a steroid receptor that is pivotal in the initiation and progression of most breast cancers. ERα regulates gene transcription through recruitment of essential coregulators, including the steroid receptor coactivator AIB1 (Amplified in Breast Cancer 1). AIB1 itself is an oncogene that is overexpressed in a subset of breast cancers and is known to play a role in tumor progression and resistance to endocrine therapy through multiple mechanisms. Here we review the normal and pathological functions of AIB1 in regards to its ERα-dependent and ERα-independent actions, as well as its genomic conservation and protein evolution. We also outline the efforts to target AIB1 in the treatment of breast cancer.